2013
DOI: 10.1155/2013/134852
|View full text |Cite
|
Sign up to set email alerts
|

Catalpol Induces Neuroprotection and Prevents Memory Dysfunction through the Cholinergic System and BDNF

Abstract: To investigate the role and mechanism of catalpol on neuroprotective effects and memory enhancing effects simultaneously, neuroprotective effects of catalpol were assessed by neurological deficits score, TTC staining, and cerebral blood flow detecting. Morris water maze was employed to investigate its effects on learning and memory and then clarify its possible mechanisms relating the central cholinergic system and BDNF. Edaravone and oxiracetam were used for positive control drugs based on its different actio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 52 publications
3
25
0
Order By: Relevance
“…Twenty-one studies used male and/or female Sprague Dawley (SD) rats; one study [14] used male Wistar rats; four studies [16, 1820] used Kunming mice. The weight of SD rats used varied from 180 g to 350 g; the weight of Wistar rats used varied from 250 g to 300 g; the weight of mice varied from 22 g to 35 g. Chloral hydrate was used to induce anesthesia in 18 studies, pentobarbital in 2 studies [21, 22], and isoflurane in 1 study [14]; while the remaining 4 studies did not report the type of anesthetics [15, 16, 23, 24]. Nineteen out of the 25 studies utilized permanent MCAO models, and the remaining six studies [14, 21–23, 25, 26] were temporary MCAO models in which ischemic time varied from 1 to 2 hours.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-one studies used male and/or female Sprague Dawley (SD) rats; one study [14] used male Wistar rats; four studies [16, 1820] used Kunming mice. The weight of SD rats used varied from 180 g to 350 g; the weight of Wistar rats used varied from 250 g to 300 g; the weight of mice varied from 22 g to 35 g. Chloral hydrate was used to induce anesthesia in 18 studies, pentobarbital in 2 studies [21, 22], and isoflurane in 1 study [14]; while the remaining 4 studies did not report the type of anesthetics [15, 16, 23, 24]. Nineteen out of the 25 studies utilized permanent MCAO models, and the remaining six studies [14, 21–23, 25, 26] were temporary MCAO models in which ischemic time varied from 1 to 2 hours.…”
Section: Resultsmentioning
confidence: 99%
“…In the control group, 14 studies applied same volume of normal saline; 3 studies [23, 28, 36] applied edible oil; one study [14] applied saline; one study [27] applied distilled water; one study [21] applied dimethyl sulfoxide; one study [37] applied 1,2-propylene glycol; 2 studies [29, 35] applied edible oil and normal saline; and 4 studies [20, 22, 26, 38] applied no treatment. Thirteen studies [14, 16, 18–22, 24, 25, 29, 31, 33, 37] adopted IV as outcome measurements; twenty-five studies used NFS as outcome measurements; and 13 studies adopted both above two outcome measurements. However, the methods used to identify IV were different; 11 studies used TTC staining and 2 studies [24, 33] used MRI scan.…”
Section: Resultsmentioning
confidence: 99%
“…Catalpol improved the memory and protected the forebrain neurons from neurodegeneration by increasing BDNF expression in the neurodegenerative mouse model produced by injecting Abeta(25-35) + ibotenic acid into the nucleus magnocellularis basalis [43], as well as increased hippocampal neuroplasticity and upregulated BDNF in aged rats [41]. Moreover, catalpol provided neuroprotection and memory enhancement through the cholinergic system and BDNF [42]. These results suggest that catalpol partially elicits antidepressant effects by attenuating or reversing CUMS-induced abnormalities in the BDNF expression.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies also indicated that the ethanol extracts of R. glutinosa and catalpol reduced the immobility time during forced swim and tail suspension tests in mice [30,39], suggesting that catalpol causes an antidepressant-like effect by regulating the central monoaminergic system. As mentioned above, BDNF and COX-2 play important roles in the pathogenesis of depression, and catalpol has already been known to stimulate BDNF and inhibit COX-2 in multiple disease models [40][41][42][43][44]. However, the therapeutic effect of catalpol on the chronic unpredictable mild stress (CUMS) model of depression and whether the antidepressant-like action of catalpol involves BDNF and COX-2 remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Fifteen days after surgery, the regional relative cerebral blood flow was quantified using Laser-Doppler flowmetry (LDF, Periflux 4001 Master, Perimed AB), and the blood flow ratio was calculated using the following formula: Blood flow ratios¼[normal (right) À ischemic (left)]/ normal (right) brain (Schabitz et al, 2003;Wan et al, 2013).…”
Section: Measurement Of Cerebral Blood Flow (Cbf)mentioning
confidence: 99%